Investigating the relationship between emotional labor levels, job satisfaction, and burnout among nurse academicians: a structural equation modeling approach - Barış Eren, Nadiye; Dinç, Leyla (Frontiers in Psychology, 2025)
BackgroundNurse academicians interact face-to-face with nursing students during the teaching process and with individuals, families, and other healthcare professionals in their practice. This study examined the relationship between emotional labor levels, job satisfaction, and burnout among nurse academicians.MethodsThis descriptive correlational study was conducted with 474 participants selected using a stratified sampling method among nursing academics working at public universities in seven geographical regions of Türkiye. Data were collected through the “Descriptive Characteristics Form,” the “Emotional Labor Scale,” the “Copenhagen Burnout Inventory,” and the “Minnesota Satisfaction Questionnaire.” Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov test, skewness and kurtosis, t-tests, one-way ANOVA, the hierarchical regression model, and path analysis (a structural equation model).ResultsNurse academicians generally demonstrated genuine acting and experienced work-related burnout; however, they had high intrinsic job satisfaction. Surface acting and deep acting differed by gender, and we observed a significant relationship between deep acting, marital status, and duration of work. Emotional labor subscales were significant predictors of burnout subscales and job satisfaction. Specifically, surface acting showed a positive association with personal, work-related, and student-related burnout (β = 0.159, p < 0.001; β = 0.192, p < 0.001; β = 0.187, p < 0.001), while genuine acting was negatively associated with the same burnout subscales (β = -0.107, p = 0.026; β = -0.123, p = 0.010; β = -0.167, p < 0.001). Deep acting (β = 0.099, p = 0.010) and genuine acting (β = 0.103, p = 0.009) positively predicted job satisfaction.ConclusionDeep acting and genuine acting had positive effects on nurse academicians’ job satisfaction, while surface acting increased burnout, genuine acting decreased burnout. Scientific activities are recommended for professional development to enhance the understanding of authentic and deep acting among nursing academics.